Financial Performance Analysis of Indonesian Sharia Commercial Bank’s Using the Islamic Index Approach in 2019-2022 - Ahmad Fauzul Hakim Hasibuan; Cheren Putri Aditya Pratama; Mustika Shahana; Khaira Khirinika (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2023)
This study aims to measure Islamic banking financial analysis using Islamicity Indices which is needed for stakeholder assessment and for future progress. The sample in this study was Islamic Commercial Banks, based on the purposive sampling method, 3 Islamic Commercial Banks were obtained including BCA Syariah Bank, Mega Syariah Bank and Muamalat Bank. In this study the data was processed using Microsoft Excel Software/Applications. The ratio will be calculated according to a predetermined formula. The results of the study show that the performance of Islamic banks in Indonesia during the 2019-2022 period has a